The Effect of Duolingo Online Application on Students’ English Vocabulary Mastery of VII Grade Class at SMP Al Razi Sinar Harapan - Khairani Mahfuza, Zulfitri (CV. PUSDIKRA MITRA JAYA, 2023)
The aim of this study was to determine the use of the Duolingo application to increase students' English vocabulary. In developing this research, the researcher implemented Duolingo through the discussion method so that it was chosen in this study to solve the problem. the method used in this research was quantitative data. The subjects of this study were 28 students of class VII SMP Al Razi Sinar Harapan with the research sample being class VII-2 as the experimental class and class VII-4 as the control class. The research instrument uses multiple choice. The results of the data show that there is a development of students' English vocabulary. This can be seen from the pre-test average for the experimental class was 53.85 and for the control class was 53.5 and the post-test average for the experimental class was 76.71 and for the control class was 67.35. From these data it can be seen that students' English vocabulary increased by using the Duolingo application as a learning medium. The research results found in this study observed t-observed 3.29 and t-table 2.05, so it can be concluded that there are differences in students' vocabulary when using the Duolingo application and without the Duolingo application. In addition, students also look active and enthusiastic about using Duolingo as a learning medium.